Bachelard’s phenomenological concept of imagination and poetic image and the question of interpretation - Adamska, Monika A. (Hybris, 2015)
This article presents some elements of the phenomenological concept of imagination and poetic image of Gaston Bachelard, in the context of their role in the collection and interpretation of literary works. Elements of other theories are also considered, the focus is particularly on the hermeneutic method, which is developing the context of phenomenological theory.